ARENA OLAHRAGA ELEKTRONIK RAMAH LINGKUNGAN DI KELAPA GADING - Thalia Remita; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2019)
According to millenials, the usage of internet is a common subject, as internet is also part of their daily life and routines. Together with the existence of internet itself, video games with the basis of using internet called